2018
DOI: 10.5935/2595-0118.20180053
|View full text |Cite
|
Sign up to set email alerts
|

Persistent idiopathic facial pain, a diagnosis and treatment of challenge. Case report

Abstract: BACKGROUND AND OBJECTIVES: Persistent idiopathic facial pain is a chronic disease with neuropathic origin, whose etiology is usually unknown; it is a medical condition that does not respond satisfactorily to drug therapy. It is also a disease with a major impact on patient quality of life and difficult to diagnose. This study aimed to report the diagnosis of a complex, persistent idiopathic facial pain, the pharmacological intervention taken and the adoption of integrative and complementary practices for the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…1 Furthermore, few controlled studies demonstrated these patients might present a poor clinical response to antidepressant use (e.g., amitriptyline and nortriptyline) and improved quality of life when associated with psychotherapy. 2 Association of PIFP and depression, anxiety symptoms, and poor quality of life are well documented in previous studies, although only a few studies about personality traits were performed. A set of stable individual characteristics (i.e., specific functioning patterns) is formed by a set of stable individual characteristics with a personal manner of perceiving oneself, other people, and life events.…”
Section: Introductionmentioning
confidence: 93%
“…1 Furthermore, few controlled studies demonstrated these patients might present a poor clinical response to antidepressant use (e.g., amitriptyline and nortriptyline) and improved quality of life when associated with psychotherapy. 2 Association of PIFP and depression, anxiety symptoms, and poor quality of life are well documented in previous studies, although only a few studies about personality traits were performed. A set of stable individual characteristics (i.e., specific functioning patterns) is formed by a set of stable individual characteristics with a personal manner of perceiving oneself, other people, and life events.…”
Section: Introductionmentioning
confidence: 93%